Cytotoxic and genotoxic effects in mechanics occupationally exposed to diesel engine exhaust (2018)
Diesel engine exhaust (DEE), which is the product of diesel combustion, is considered carcinogenic in humans. It comprises toxic gases, polycyclic aromatic hydrocarbons (PAHs) and particulate matter which can reach the pulmonary parenchyma and trigger various diseases, including cancer. The aim of the present study was to evaluate the potential cytotoxic and genotoxic effects of DEE exposure on peripheral blood and buccal epithelial cells in mechanics occupationally exposed to DEE. We recruited 120 exposed mechanics and 100 non-exposed control individuals. Significant differences were observed between the two groups in terms of percentage of tail DNA and damage index (DI) in the alkaline comet assay; levels of biomarkers by cytokinesis-block micronucleus cytome (CBMN-Cyt) assay; frequency of micronucleus (MN), nucleoplasmic bridge (NPB), nuclear bud (NBUD) and apoptotic cells (APOP) and levels of biomarkers for micronucleus, karyorrhexis (KRX), karyolysis (KRL) and condensed chromatin (CC) by the buccal micronucleus cytome (BM-Cyt) assay. A significant and positive correlation was found between the frequency of MN in lymphocytes and buccal cells in the exposed group. We found a significant correlation between age and percentage of tail DNA and DI in the comet assay, APOP and MN in the CBMN-Cyt assay and NBUD and MN in the BM-Cyt assay. Furthermore, we found a positive and significant correlation of MN frequency in lymphocytes and buccal cells and age and MN frequency in lymphocytes with the time of service (years). Regarding lifestyle-related factors, a significant correlation was observed between meat and vitamin consumption and NBUD formation on CBMN-Cyt and between meat consumption and MN occurrence on CBMN-Cyt. Of the BM-Cyt biomarkers, there was a correlation between alcohol consumption and NBUD formation and between binucleated cell (BN), pyknosis (PYC), CC and KRL occurrence and family cancer history. These data showed the usefulness of biomarkers of the comet, CBMN-Cyt and BM-Cyt assays for human biomonitoring and evaluation of cancer risk in the exposed populations.